Edukasi Keuangan Islami Sejak Usia Dini sebagai Pondasi Kepemimpinan Masa Depan - Desy Arigawati; Muhamat Suhaendi; Sayadi Mahmud; Firda Celiana Bahri; Nadia Inayatul Ulya Al − Husna; Raden Nanda Maharditya; Hasby Mauriza Ash − Sidiqi; Nara Praba Wardaya; Riza Ilham Arifin; Muhammad Fahrul Al Qadri; Triandanu Adi Setyawan; Angga Dwiyanto Simamora; Bintang T. P. Sinaga; Yudi Tri Wibowo (FKIP, Universitas Palangka Raya, 2026)
In the era of globalization, children are exposed to a social environment influenced by external factors such as social media, advertising, and a consumer culture, all of which can promote a materialistic lifestyle. Consequently, financial literacy education has become essential to equip children with the necessary skills to manage their finances effectively. Beginning with a simple understanding of accounting, children can learn fundamental concepts of money management, financial decision-making, and planning. However, many young children still lack access to this vital education. Various learning methods and media, including loose parts, storytelling, and interactive educational tools, can be utilized to foster financial understanding. Additionally, this education promotes important social concepts like sharing, charity, and the responsibility of managing finances to help others. It integrates Islamic principles, emphasizing values such as honesty, justice, transparency, and the avoidance of usury. Through these principles, children are not only taught how to manage their personal finances but also how to contribute to society. By implementing financial literacy education at an early age, we can help children grow into informed, ethical, and responsible leaders in the future. This education is crucial for ensuring they make sound financial choices and contribute positively to their communities.